Raise the anchor! Synthesis, X-ray and NMR characterization of 1, 3, 5-triazinanes with an axial tert-butyl group. Issue 41 (19th August 2020) - Kletskov, Alexey V.; Zatykina, Anastasya D.; Grudova, Mariya V.; Sinelshchikova, Anna A.; Grigoriev, Mikhail S.; Zaytsev, Vladimir P.; Gil, Diego M.; Novikov, Roman A.; Zubkov, Fedor I.; Frontera, Antonio
Abstract : N-t -Bu- N ′, N ′′-Disulfonamide-1, 3, 5-triazinanes were synthesized and studied by X-ray single crystal structure analysis and dynamic low-temperature NMR. Abstract : N-t -Bu- N ′, N ′′-Disulfonamide-1, 3, 5-triazinanes were synthesized and characterized by X-ray single crystal structure analysis. In the course of the X-ray structure elucidation, the first solid experimental evidence of the axial position of the tert -butyl group in unconstrained hexahydro-1, 3, 5-triazacyclohexanes was obtained. Dynamic low-temperature NMR analysis allowed to fully investigate a rare case of crystallization-driven unanchoring of the tert -butyl group in the chair conformation of saturated six-membered cycles. DFT calculations show that the use of explicit solvent molecules is necessary to explain the equatorial position of the t -Bu group in solution. Otherwise, the axial conformer is the thermodynamically stable isomer.